Sanger Validation of High-Throughput Sequencing in Genetic Diagnosis: Still the Best Practice? - De Cario, Rosina; Kura, Ada; Suraci, Samuele; Magi, Alberto; Volta, Andrea; Marcucci, Rossella; Gori, Anna Maria; Pepe, Guglielmina; Giusti, Betti; Sticchi, Elena (Frontiers in Genetics, 2020)
Next-generation sequencing (NGS)’s crucial role in supporting genetic diagnosis and personalized medicine lead to the definition of Guidelines for Diagnostic NGS by the European Society of Human Genetics. Factors of different nature producing false-positive/negative NGS data together with the paucity of internationally accepted guidelines providing specified NGS quality metrics to be followed for diagnostics purpose, made the Sanger validation of NGS variants still mandatory. We reported the analysis of 3 cases of discrepancy between NGS and Sanger sequencing in a cohort of 218 patients. NGS was performed by Illumina MiSeq® and Haloplex/SureSelect protocols targeting 97 or 57 or 10 gene panels usually applied for diagnostics. Variants called following guidelines suggested by the Broad Institute and identified according to MAF<0.01 and allele balance >0.2 were Sanger validated. Three out of 945 validated variants showed a discrepancy between NGS and Sanger. In all 3 cases a deep evaluation of the discrepant gene variant results and methodological approach allowed to confirm the NGS datum. Allelic drop-out (ADO) occurrence during polymerase chain or sequencing reaction was observed, mainly related to incorrect variant zygosity. Our study extends literature data in which almost 100% “high quality” NGS variants are confirmed by Sanger; moreover, it demonstrates that in case of discrepancy between a high quality NGS variant and Sanger validation, NGS call should not be a priori assumed to represent the source of the error. Actually, difficulties (i.e. ADO, unpredictable presence of private variants on primer-binding regions) of the so called “gold standard” direct sequencing should be considered especially in light of the constantly implemented and accurate high-throughput technologies. Our data along with literature, raise a discussion on the opportunity to establish a standardized quality threshold by International Guidelines for clinical NGS in order to limit Sanger confirmation to borderline conditions of variant quality parameters and verification of correct gene variant call/patient coupling on a different blood sample aliquot.